Potensi Pengembangan Ternak Sapi Potong Berbasis Ketersediaan Hijauan Pakan Di Pulau Sulabesi Kabupaten Kepulauan Sula - Irfandi Norau; Yusnaini Yusnaini; Abdurahman Hoda (Jurnal Pertanian Khairun, 2023)
Beef cattle have good prospects to be developed in Indonesia. Forage providing has potential to support the maintenance of beef cattle. This study aims to (1) study the characteristics of beef cattle breeders in Sulabesi island (2) identify and analyze the potential of beef cattle development and beef cattle development strategies. (3) analyze the condition of strategic areas, natural resources, and beef cattle rearing systems for the development of beef cattle, and (4) analyze opportunities, constraints, supporting factors and challenges in order to formulate a development strategy based on internal factors and external factors that can affect the development of beef cattle. This research was conducted on Sulabesi Island from October to December 2022. The characteristics of beef cattle breeders were analyzed by using descriptive statistics. The state of the region that is a sector basis non basis was analyzed by using LQ (Location Quation). Beef cattle development potential was analyzed by using KPPTR and SWOT analysis. The results shows that the farmers in the location were of productive age and had a good education. The types of forages found are very diverse. West Sulabesi, Central Sulabesi and South Sulabesi sub-districts are potential beef cattle bases with LQ values of 2.19, 1.96 and 1.38. There are two subdistricts with very good livestock capacity, namely Sanana District with 45,924 ST and North Sanana District with 32,543 ST. The score of the IFE matrix is 1.10 and the EFE is 1.11 where these two points are in quadrant 1 of the SWOT matrix. In determining the strategy, there are 3 alternative S-O strategies, 4 alternative W-O, 3 S-T and 2 W-T strategies.Key words: Forage, breeder, Sulabesi Island, Beef Cattle, LQ, KPPTR, SWOT.